Te Rito o Te Harakeke: Decolonising Child Protection Law in Aotearoa New Zealand - Fitzmaurice-Brown, Luke (Victoria University of Wellington Law Review, 2023)
It is now firmly established that the overrepresentation of tamariki Māori within the Aotearoa New Zealand child protection system is largely a consequence of colonisation. However, at least as far as the Crown is concerned, the contention that decolonisation is a necessary step in reversing those trends remains a more controversial issue. Drawing on my doctoral research into this topic, this article argues that the child protection system must be decolonised, and that efforts towards reform which do not prioritise decolonisation are likely to perpetuate long-standing harms. The article has four goals. First, I examine why decolonisation provides the best framework through which to enact child protection system reform. Secondly, I identify three overarching themes within the current legal framework, but argue that the presence of these themes does not mean they are all given equal weight. Thirdly, I outline a theory of reform I have termed "kaupapa Māori legal theory", which seeks to enable legislative change based on tikanga Māori in a way which pays heed to the risks of doing so from a Māori perspective. Finally, I apply that theory to child protection law, identifying six tikanga principles which could provide the basis of a decolonised system: mana, rangatiratanga, wānanga, whānau, whakapapa and whanaungatanga.